2002
DOI: 10.1034/j.1600-0412.2002.810513.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum SCC, CA125, and CA19‐9 levels and lymph node status in squamous cell carcinoma of the uterine cervix

Abstract: Combination assay of pretreatment serum SCC and CA125 levels seems to be useful in estimating lymph node status and the prognosis for patients with cervical SCC in a preoperative setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 16 publications
2
56
2
1
Order By: Relevance
“…More candidates should be enroled in further studies to realise the differences of serum levels of IGF-1 between normal individuals, patients with precancer lesions and cervical cancer. Pretreatment SCC Ag or CEA assays, as tumour-associated antigens, have been identified to be valuable in distinguishing high-risk patients requiring adjuvant therapy and in predicting prognosis in early-stage cervical cancer (Bae et al, 1997;Takeda et al, 2002;Reesink-Peters et al, 2005). In our cohorts, the integration of SCC Ag level and IGF-1R overexpression or the combination of CEA and IGF-1 levels could produce more accurate estimates in identifying patient subgroups of poor prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…More candidates should be enroled in further studies to realise the differences of serum levels of IGF-1 between normal individuals, patients with precancer lesions and cervical cancer. Pretreatment SCC Ag or CEA assays, as tumour-associated antigens, have been identified to be valuable in distinguishing high-risk patients requiring adjuvant therapy and in predicting prognosis in early-stage cervical cancer (Bae et al, 1997;Takeda et al, 2002;Reesink-Peters et al, 2005). In our cohorts, the integration of SCC Ag level and IGF-1R overexpression or the combination of CEA and IGF-1 levels could produce more accurate estimates in identifying patient subgroups of poor prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…Zhang et al [6] also studied the biomarkers CA19-9, CA15-3 and their statistical correlation was not significant in Ovarian Cancer and did not corresponded with the clinical course of the disease. Vistintin et al [7] found the levels of leptin, prolactin, osteopontin to be 95% sensitive and 99% specific in Ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although Gaarenstroom et al suggested a relationship between pre-treatment Cyfra 21-1, TPA, SCC antigen levels and tumor size, and concluded that this was insufficient for identifying patients at risk for the presence of lymph node metastases or parametrial involvement (9), Taketa et al stated that pre-treatment analysis of the DTM index (double-tumor marker index) of SCC and CA125 levels allows estimation of lymph node status and prognosis for patients with cervical squamous cell carcinoma (13). In this study we were able to further these findings by showing that there was a significant relationship between the two tumor markers and the prognostic factors FIGO stage, lesion size, lymph node metastasis, and parametrial involvement.…”
Section: Discussionmentioning
confidence: 99%